2003
DOI: 10.1111/j.1550-7408.2003.tb00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Plateins: A Novel Family of Signal Peptide‐Containing Articulins in Euplotid Ciliates1

Abstract: In euplotid ciliates, the cortex is reinforced by alveolar plates--proteinaceous scales located within the membranous alveolar sacs, forming a monolayer just below the plasma membrane. This system appears to play a cytoskeletal role analogous to that provided by the fibrous epiplasm found beneath the cortical alveoli in other ciliates. In Euplotes aediculatus, the major alveolar plate proteins (termed alpha-, beta-, and gamma-plateins) have been identified. Using anti-platein antibodies, an expression library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…1A; see Fig. S2A) but similar to that of plateins-which are also CRMPs-from Euplotes aediculatus (21). Colabeling with tubulin demonstrates that TtALV2 is excluded from the circumciliary ring region and absent from the oral apparatus ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…1A; see Fig. S2A) but similar to that of plateins-which are also CRMPs-from Euplotes aediculatus (21). Colabeling with tubulin demonstrates that TtALV2 is excluded from the circumciliary ring region and absent from the oral apparatus ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Each group of transporters possessed both up- and down-regulated members, with the top up-regulated genes were predominantly ABC-type, ion, nutrient and nuclear transporters that were mostly resumed to near normal levels in 5 h. The highly down-regulated genes were predominantly vacuolar ATPase subunits that remained down-regulated in 5 h. The increased expressions of several oocyst wall proteins; articulin proteins that are known to be important in maintaining cell shapes in Euglena and ciliates [26,27], and mucin-like proteins suggestive of active repairing on some cell/oocyst surface molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Articulins are part of the membrane skeleton of eukaryotic cells stabilizing plasma membranes [45,46]. It is suggested that ESTs PM265 and PM269, function as plateins, a new family of articulins described by Kloetzel et al [47]. Plateins contain modified articulin core domains typical of secreted structural proteins as well as a novel predicted signal peptides detected in intra-alveolar sacs, an extracellular environment.…”
Section: Discussionmentioning
confidence: 99%